Socio-economic and cultural factors associated with smoking prevalence among workers in the National Health System in Belo Horizonte - Luiz Fábio Machado Barbosa; Carla Jorge Machado (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVE: To identify factors related to smoking among health workers of the National Health System in Belo Horizonte, Minas Gerais, Brazil. METHODS: A cross-sectional study based on a survey conducted between September 2008 and January 2009 with a stratified sample. Data on sociodemographic, health, employment, and work characteristics were analyzed. Poisson regression models with robust variance and estimation of unadjusted and adjusted prevalence ratios were used to establish associations at a 5% significance level for inclusion in the final model. RESULTS: In 1,759 questionnaires analyzed, in which the question related to smoking was answered, the overall prevalence of smoking was 15.7%. Reasonable relationship between requirements and available resources remained negatively correlated to smoking in the final model (PR = 0.75; 95%CI 0.58 - 0.96). The variables that remained positively associated with smoking were being male (PR = 1.75; 95%CI 1.36 - 2.25) and the following positions: community health workers (PR = 2.98; 95%CI 1.76 - 5.05), professionals involved in monitoring (PR = 3.86; 95%CI 1.63 - 5.01), administrative and other general services workers (PR = 2.47; 95%CI 1.51 - 4.05); technical mid-level workers (PR = 2.23; 95%CI 1.31 - 3.78), including nurses and practical nurses (PR = 2.07; 95%CI 1.18 - 3.64). CONCLUSION: Specific occupational subgroups were identified and should be prioritized in smoking cessation and prevention programs.